2012
DOI: 10.1140/epjc/s10052-012-1871-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantum deformation of the angular distributions of synchrotron radiation. Emission from particles in the first excited state

Abstract: The exact expressions for the characteristics of synchrotron radiation of charged particles in the first excited state are obtained in analytical form using quantum theory methods. We performed a detailed analysis of the angular distribution structure of radiation power and its polarization for particles with spin 0 and 1/2. It is shown that the exact quantum calculations lead to results that differ substantially from the predictions of classical theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Classical theory predicts the concentration of radiation near orbits' plane in ultrarelativistic limit. It was shown [4,5] that for first excited state particles (no matter spinor or scalar) quantum theory does not confirm this assumption. Here we demonstrated that for the case of shortest quantum spectrum no radiation concentration is observed.…”
Section: Effective Angles Of Radiationmentioning
confidence: 99%
“…Classical theory predicts the concentration of radiation near orbits' plane in ultrarelativistic limit. It was shown [4,5] that for first excited state particles (no matter spinor or scalar) quantum theory does not confirm this assumption. Here we demonstrated that for the case of shortest quantum spectrum no radiation concentration is observed.…”
Section: Effective Angles Of Radiationmentioning
confidence: 99%
“…Ref. [8]) and thus can significantly change classical results (which may be the subject of a separate study).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, in addition to giving an exact analytical proof for the presence of π-component in the plane of motion, we established the physical cause of this phenomenon. For the particular case of a one-harmonic spectrum, this proof can be found in our recent papers [114,115].…”
Section: )mentioning
confidence: 80%